Electrodeposited Cu Nanofoam Structures for Electrochemical CO2 Reduction - Birutė Serapinienė; Laima Gudavičiūtė; Rimantas Ramanauskas (Proceedings, 2023)
An exclusive Cu surface feature has the ability to convert CO2 into hydrocarbons with significant Faradaic efficiency [...]